Metabolic syndrome in rural Australia: An opportunity for primary health care - Jancey, Jonine; James, Anthony; Lee, Andy; Howat, Peter; Hills, A.; Anderson, A.; Bordin, C.; Blackford, Krysten (2019)
Objective: To measure the impact of a 6-month home-based behaviour change intervention on reducing the risk of chronic disease as determined by metabolic syndrome status and cardiovascular risk score, and discuss implications for primary care in rural areas. Design: A two-arm randomised controlled trial of rural adults. Setting: The rural town of Albany in the Great Southern region of Western Australia. Participants: Participants (n = 401) aged 50-69 years who were classified with or at risk of metabolic syndrome and randomly assigned to intervention (n = 201) or waitlisted control (n = 200) group. Interventions: A 6-month intervention program incorporating goal setting, self-monitoring and feedback, with motivational interviewing was conducted. Main outcome measures: Change in metabolic syndrome status and cardiovascular risk. Results: Significant improvements in metabolic syndrome status and cardiovascular disease risk score (−0.82) were observed for the intervention group relative to control group from baseline to post-test. Conclusion: This home-based physical activity and nutrition intervention reduced participants' risk of experiencing a cardiovascular event in the next 5 years by 1%. Incorporating such prevention orientated approaches in primary care might assist in reducing the burden of long-term chronic diseases. However, for realistic application in this setting, hurdles such as current national health billing system and availability of resources will need to be considered.